Aesthetic Deviation: Victor Segalen in China - Kimberley Healey (Studies in 20th & 21st Century Literature, 2003)
Victor Segalen's early twentieth-century writings on China provide an alternative to nineteeth-century French literary exoticism. In his examination of the self and the other, much admired by postcolonial critics, he attempts to embrace a new aesthetics of diversity. Segalen's writing on the other opens the door to a jarring and heterogeneous aesthetic of exotic encounter by reevaluating the position of the European abroad as well as the literary forms used to depict the foreign. However, Segalen's encounters with difference as illustrated in his two main narratives on China, Equipée and René Leys, deviate from the desire for absolute difference outlined in his theoretical work, Essay on Exoticism. Although seeking experiences of the real that will plunge the traveler into an awareness of difference, his narratives of diversity ultimately reveal greater gaps between the self and other that must be bridged by the text.
Keywords: Victor Segalen; twentieth-century; nineteeth-century French literary exoticism; exoticism; orientalism; China; self; other; the other; postcolonial critics; diversity; heterogeneous aesthetic; exotic; European abroad; foreign; Equipée; René Leys; Essay on Exoticism; experiences of the real; real; experience; traveler; difference